Conservative treatment of adolescent idiopathic scoliosis (AIS): A narrative review of current evidence and implications for clinical practice - Błachnio, Klaudia; Kopciał, Szymon; Piecuch, Dawid; Hańczyk, Edyta (Quality in Sport, 2024)
Introduction and purpose: Adolescent idiopathic scoliosis (AIS) is characterized by lateral curvature, vertebral rotation, and disruption of physiological curvature of the spine with the Cobb angle ≥10°. AIS affects 1-3% of children aged 10-16 years, representing the most common form of idiopathic scoliosis. Diagnosis of AIS is by exclusion and can be suspected based on Adams forward bend test and scoliometer. Untreated AIS can lead to serious consequences, such as progression of the deformity, back pain, reduced respiratory and cardiovascular function. The aim of this review is to update overview of conservative treatment options. Description of the state of knowledge: AIS treatment guidelines from the Scoliosis Research Society (SRS) and the Scientific Society on Scoliosis Orthopaedic and Rehabilitation Treatment (SOSORT) advocate for observation, bracing, or surgery depending on curve severity, with a focus on avoiding spinal fusion when possible. Additionally, SOSORT recommends scoliosis-specific physiotherapy exercises for smaller curves or as an adjunct to bracing. Conservative treatment aims to prevent curve progression, manage respiratory and spinal complications, and improve quality of life. Conclusions: AIS can significantly impair the physical and psychosocial well-being of young patients, with potential long-term consequences extending into adulthood Individualized treatment plans and patient/parent education are crucial for optimal outcomes. Schroth exercises are superior to Core Stabilization (CS) exercises in reducing Cobb angle, trunk rotation and improving spinal mobility, cosmetic trunk deformities and quality of life. CS exercises are more effective in increasing peripheral muscle strength, reducing pain and correcting vertebral rotation.